PPP Strikes Back : Aggregation and the Real Exchange Rate - Mumtaz, Haroon (IMF Working Papers; Working Paper ;, 2003)
We show the importance of a dynamic aggregation bias in accounting for the PPP puzzle. We prove that established time-series and panel methods substantially exaggerate the persistence of real exchange rates because of heterogeneity in the dynamics of disaggregated relative prices. When heterogeneity is properly taken into account, estimates of the real exchange rate half-life fall dramatically, to little more than one year, or significantly below Rogoff's "consensus view" of three to five years. We show that corrected estimates are consistent with plausible nominal rigidities, thus, arguably, solving the PPP puzzle.